Steuerwettbewerb und Finanzverfassung - Klaus Beckmann; Dennis Engelmann (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2008)
This paper surveys the nexus between tax competition and the fiscal constitution. We distinguish various approaches to competition between jurisdictions and provide a critique of evolutionary approaches to 'systems competition'. In the main part of the paper, a simple model of horizontal tax competition, based on the Zodrow-Mieszkowski- approach, is developed that can be extended to address 'reasons for rules' in a tax competition context. Specifically, we discuss the internalisation of fiscal externalities in a federation and the timing of tax policy decisions, extending the existing literature in the latter regard. Several tentative constitutional recommendations are derived.
urn:nbn:de:gbv:705-opus-17207
Keywords: H73; 330; Steuerwettbewerb; Finanzverfassung; Institutioneller Wettbewerb; Finanzföderalismus; Theorie; OECD-Staaten